EVALUASI KINERJA PEGAWAI NEGERI SIPIL DI ERA PANDEMI COVID-19 - Syafutri, Maulida; Sulistio, Eko Budi; Atika, Dewie Brima (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
During the Covid-19 pandemic, the government implemented the WFH (word from home) policy, which is one of the government policies with a work model where employees work at home with the help of telecommunications technology as a work system used for employees. As for all the components of the KUA strategy for the city of Bandar Lampung, they are still in planning and all components of the strategy have not been realized due to limited resources, both human resources and other resources, such as limited sources of aid funds from the government. This has had an impact on all the programs planned by the KUA in Bandar Lampung City so that not all of them have been implemented properly. The results of this study are that the performance of Civil Service Employees of the City of Bandar Lampung in the Covid-19 pandemic era has not carried out their duties and authorities to the fullest so that the service process has not run optimally as can be seen from the timeliness and independence carried out by the apparatus. maximum because there are still many of the apparatus who are not competent in carrying out their duties and the online service system sometimes still experiences problems such as the network and website pages provided so that there needs to be improvement and efforts from the government in dealing with existing problems.